A implementação da sistematização da assistência de enfermagem em uma instituição de longa permanência para idosos - Menegócio, Alexandro Marcos (2008)
The focus of this research-action was to develop a systematization model of nursing assistance and its implementation in a private Long-Permanence Institution for Elderly People (ILPI), in the city of Salto, State of São Paulo, aiming the growth of the elderly population which lives in collective housings. The knowledge concerning the aging process alterations becomes necessary, as well as the understanding of the specifications and fragilities of this stage of life, especially for the health professionals, so that they act in a humanized, systemized and individualized way. The SAE is an organized and sequential form used for the nursing assistance planning. Using the SAE means getting identity and professional autonomy, so that when the nursing diagnosis is fulfilled it establishes the scientific character of the singular and planned assistance. The methodology used was of quanti-qualitative nature, having as its main methodological procedure the research-action. Both, the Katz Index and the Mini-Mental-Examination were adapted to the reality of the institution and applied. The collection of data was carried through among the 33 residents, being 17 males and 16 females, between the ages of 60 and 85 years old, that were found in the institution during the period. The study was conducted in five stages: visits to the ILPI, elaboration of a data collection instrument, analysis of the data and implementation of the compact form of the subsequent phases of the SAE and evaluation of the nursing professionals. The technique of focal group was also used with four professionals of the institution, in order to have a previous evaluation of the systematization implement of the nursing assistance. It was observed that the implementation of the SAE contributes for a better care toward the elderly, as well as for the health professionals. The variables sex, age, time of institutionalization, nursing problems, basic human needs affected, nursing diagnostic and levels of dependence were pointers that guided the elaboration of projects that serve to take care of the main basic human needs affected of this ILPI residents